Partisipasi Masyarakat Dalam Pelaksanaan Program Kampung KB di Kelurahan Air Dingin Kecamatan Bukit Raya Kota Pekanbaru - Winda Dwi Amanda; Zulkarnaini Zulkarnaini (Journal of Research and Development on Public Policy, 2024)
The Family Quality Village Program is an initiative to improve the quality of life of communities at the village level or similar in order to create small, prosperous and quality families. The level of community participation plays an important role in determining the success of the KB Village Program. This study aims to explore the level of community participation in the implementation of the KB Village Program and to identify factors that hinder community participation in Air Dingin Village, Bukit Raya Subdistrict, Pekanbaru City. The theory that forms the basis of this research is Dwiningrum's theory which carries 4 indicators, namely participation in decision making, participation in implementation, participation in utilization of results, and participation in evaluation. The research method used is qualitative with a descriptive approach, and data collection through observation, interviews, and documentation which is then analyzed based on the problems identified in the research. The findings of this research show that although the KB Village Program in Air Dingin Village is already running, it still does not involve the community as a whole. The main obstacles in this program are budget limitations and lack of community enthusiasm.